Ethylene-Mediated Acclimations to Flooding Stress. Issue 1 (20th April 2015) - Sasidharan, Rashmi; Voesenek, Laurentius A.C.J.
Abstract : The volatile hormone ethylene is an important regulator of plant-adaptive responses to flooding stress. Abstract: Flooding is detrimental for plants, primarily because of restricted gas exchange underwater, which leads to an energy and carbohydrate deficit. Impeded gas exchange also causes rapid accumulation of the volatile ethylene in all flooded plant cells. Although several internal changes in the plant can signal the flooded status, it is the pervasive and rapid accumulation of ethylene that makes it an early and reliable flooding signal. Not surprisingly, it is a major regulator of several flood-adaptive plant traits. Here, we discuss these major ethylene-mediated traits, their functional relevance, and the recent progress in identifying the molecular and signaling events underlying these traits downstream of ethylene. We also speculate on the role of ethylene in postsubmergence recovery and identify several questions for future investigations.